Washington View: Education + Money = Freedom. (October 2020) - Ferguson, Maria
The COVID-19 pandemic and related economic downturn has made the persistent inequities in the U.S. education system even more evident than before. In her monthly Kappan column, Maria Ferguson discusses how approaches to school spending have failed to respond adequately and fairly to economic conditions. On top of the differences in funding is the phenomenon of wealthy parents spending their money to find ways out of the system by, for example, creating pandemic pods that enable their children to have in-person learning opportunities that aren't likely to be available for poorer children. Examples like this may look like "education freedom, " but it's freedom only available for a few .